FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PELAPORAN WAJIB PAJAK DOSEN TETAP UNIVERSITAS TARUMANAGARA DI JAKARTA - Sofia Prima Dewi, Keni Keni (Jurnal Akuntansi, 2012)
The purpose of this research is to examine the effect of taxpayer awareness, knowledge and understanding of tax laws, perceptions of the effectiveness of the tax system   and   the   willingness   to   pay   taxes   on   taxpayer   reporting   compliance Tarumanagara University lecturer in Jakarta. Data analysis of 104 respondents conducted with the help of PASW Statistics program version 18.00. The results showed that knowledge and understanding of tax laws and the willingness to pay taxes have a significant effect on taxpayer compliance reporting while the taxpayer awareness and perceptions of the effectiveness of the tax system does not have a significant impact on taxpayer compliance reporting.